2019
DOI: 10.1080/21645515.2019.1662267
|View full text |Cite
|
Sign up to set email alerts
|

Dose effect of influenza vaccine on protection against laboratory-confirmed influenza illness among children aged 6 months to 8 years of age in southern China, 2013/14–2015/16 seasons: a matched case–control study

Abstract: Background We conducted a matched case-control study in China during the 2013/14-2015/16 influenza seasons to estimate influenza vaccine effectiveness (VE) by dose among children aged 6 months to 8 years. Methods Cases were laboratory-confirmed influenza infections identified through the influenza-like illness sentinel surveillance network in Guangzhou. Age-and sex-matched community controls were randomly selected through the expanded immunization program database. We defined priming as receipt of ≥1 dose of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“… 17 , 18 The national pharmacopoeia of China recommends that children aged <3 years receive the 0.25 mL dose (containing 7.5 μg hemagglutinin per virus strain) of any influenza vaccine, while globally a 0.5 mL dose (containing 15 μg hemagglutinin per virus strain) of influenza vaccine is more widely recommended in this age group. 19 Our study showed that the safety profiles of Shz QIV (0.25 mL) and Shz QIV (0.5 mL) were similar after the first and the second injections in those aged 6–35 months, suggesting that the increased dose does not compromise safety in this age group. HAI antibody responses were slightly higher for Shz QIV (0.5 mL) than Shz QIV (0.25 mL) and non-inferiority of the 0.25 mL dose for the B/Victoria-like strain was not shown.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“… 17 , 18 The national pharmacopoeia of China recommends that children aged <3 years receive the 0.25 mL dose (containing 7.5 μg hemagglutinin per virus strain) of any influenza vaccine, while globally a 0.5 mL dose (containing 15 μg hemagglutinin per virus strain) of influenza vaccine is more widely recommended in this age group. 19 Our study showed that the safety profiles of Shz QIV (0.25 mL) and Shz QIV (0.5 mL) were similar after the first and the second injections in those aged 6–35 months, suggesting that the increased dose does not compromise safety in this age group. HAI antibody responses were slightly higher for Shz QIV (0.5 mL) than Shz QIV (0.25 mL) and non-inferiority of the 0.25 mL dose for the B/Victoria-like strain was not shown.…”
Section: Discussionmentioning
confidence: 50%
“…In those who were previously unvaccinated, the second dose of Shz QIV elicited higher HAI antibody responses than after the first, suggesting that a schedule of two doses, 4 weeks apart would be more appropriate for previously unvaccinated children in this age range. However, the Chinese national pharmacopoeia recommends that children aged 3–8 years receive one dose irrespective of previous influenza vaccination history, 19 which is inconsistent with guidelines by the Chinese Center for Disease Control and Prevention, 22 and those by the World Health Organization 23 and the Advisory Committee on Immunization Practices (ACIP) in the USA. 24 …”
Section: Discussionmentioning
confidence: 99%
“…29 In the 2013-2014, 2014-2015, and 2015-2016 seasons, vaccination rates for children 6-96 months old were 18.0%, 13.5%, and 10.0%, respectively. 30 Our study then showed a 1.0% rate in the 2019-2020 season. Growing vaccine hesitancy 31 has prevented reaching and maintaining high vaccination coverage.…”
Section: Discussionmentioning
confidence: 50%
“…The search terms identified 1408 studies from the six databases—282 from the Wanfang database, 472 from CNKI, 302 from VIP journal database, 282 from CBM, 130 from Web of Science, and 27 from PubMed. Our eligibility review identified 21 articles for including in the analyses [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] ( Figure 1 ). The 21 eligible studies were conducted between the 2010–2011 influenza season and the 2017–2018 influenza season.…”
Section: Resultsmentioning
confidence: 99%